Industrializing Additive Manufacturing - Proceedings of Additive Manufacturing in Products and Applications - AMPA2017 (Springer International Publishing, 2018)
These proceedings exchange ideas and knowledge among engineers, designers and managers on how to support real-world value chains by developing additive manufactured series products. The papers from the conference show a holistic, multidisciplinary view.